2017
DOI: 10.15407/fz63.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Endogenous Hydrogen Sulfide Synthesis Inhibits Mitochondrial Permeability Transition Pore Opening and Restores Constitutive No-Synthase Coupling in Old Rat Heart

Abstract: Вивчали вплив кофактора H 2 S-синтезувальних ферментів -піридоксаль-5-фосфату (П5Ф) на чутливість мітохондріальної пори (МП) до дії природного її індуктора Са 2+ у серці старих щурів, а також на вміст H 2 S та показники оксидативно-нітрозативного стресу в мітохондріях серця. Показано, що у старих тварин розвивається оксидативний і нітрозативний стрес, що супроводжується зниженням індексу спряження конститутивної Са . Застосування П5Ф пригнічувало Са 2+ -індуковане відкривання МП через зменшення чутливості до ї… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Statistical calculations were performed using the "StatisticSoft 6.0" program. [19]. The concentration of peroxynitrite rose by 55.5%.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Statistical calculations were performed using the "StatisticSoft 6.0" program. [19]. The concentration of peroxynitrite rose by 55.5%.…”
Section: Methodsmentioning
confidence: 95%
“…It is considered that any increase in О 2 production (by mitochondria, xanthine oxidase, or NADPH-oxidase) leads to cNOS uncoupling. This cNOS becomes not only a powerful О 2 generator by itself, but at the same time it activates other sources of О 2 - [19]. Peroxynitrite concentration was measured by using its reaction with potassium iodide under pH 7.0 in 0.2 M phosphate buffer with the same pH [17].…”
Section: Methodsmentioning
confidence: 99%
“…Increased vascular tone and increased resistance of the vascular wall to blood fl ow with age may occur due to impaired synthesis of vasodilator molecules, in particular such as Nitric Oxide (NO) and hydrogen sulfi de (H 2 S). It has been shown that under oxidative stress, which progresses with hypertension and aging, the production of gas transmitters is signifi cantly reduced [10][11][12]. Therefore, in the work aimed at the treatment or prevention of these diseases, decrease of markers of oxidative stress and restoration of glutathione levels is considered a promising target.…”
Section: Introductionmentioning
confidence: 99%